Analysis of dissolution kinetics of narrow polydispersity poly(4-hydroxystyrene) in alkaline aqueous solution using machine learning. (28th May 2021) - Tanaka, Naoki; Watanabe, Kyoko; Matsuoka, Kyoko; Azumagawa, Kazuki; Kozawa, Takahiro; Ikeda, Takuya; Komuro, Yoshitaka; Kawana, Daisuke
Abstract: Understanding the dissolution kinetics of resist materials is essential for their efficient development. In this study, we investigated the dissolution kinetics of poly(4-hydroxystyrene) (PHS) with a weight-average molecular weight ( M w ) of 8000–30 000 and a polydispersity index ( M w /M n ) of 1.07–1.20. The dissolution kinetics of PHS films was observed in tetramethylammonium hydroxide (TMAH) aqueous developers by a quartz crystal microbalance (QCM) method. The TMAH concentration was changed from 0 to 2.38 wt%. The formation of a thick transient swelling layer at these M w /M n values was suppressed compared with that at M w /M n  > 2. QCM data were analyzed using the polynomial regression to clarify the effects of M w and M w /M n on the dissolution kinetics in a narrow polydispersity region. Both dissolving and swelling kinetics largely depended on M w / M n . M w had little effect in 2.38 wt% TMAH developer; however, it had a large effect on the swelling when 2.38 wt% TMAH developer was diluted.